Bleeding in orthopedic surgery: role of blood transfusion and erythropoietin alpha - Soviero, F.; Geraci, A.; Termine et al., S. (Acta Biomedica Atenei Parmensis, 2010)
High energy trauma is often responsible for acute bleeding. Long bone and pelvis fractures are correlated with increased blood loss. Hypovolaemia could become a life threatening complication especially in elderly patients because of the reduced physiological response. Furthermore it could compromise the course of associated morbidities. Haemorrage is also associated in both comminuted fractures and osteoporosis. An increased intraoperative bleeding often occurs when a prolonged surgical time is required to obtain an appropriate ostheosynthesis. The final consequence of a mayor bleeding is hypovolaemic shock. The reduced oxygen tension of the tissue may be responsible for  heart attack, arrhythmia, stroke, multi organ deficiency. For these reasons, it is important to immediately recognize and correct all potential bleeding in order to avoid complications.